A influência de variáveis ambientais na distribuição espacial local em comunidade de peixes de recife costeiros do nordeste do Brasil - Grande, Henrique (2012)
A major goal in ecology study is to understand and identify what mechanisms can determine the heterogeneous distribution of the communities, so the spatial pattern is a key point to understand what factors are responsible for the distribution and abundance of organisms. In reef fishes, the community structure can be attributed to different biotic and abiotic factors observed at different spatial scales. The present study identified environmental factors that explain the reef fish community structure in a project structured in different spatial units, hierarchically designated on a local scale. The three spatial scales examined were tens of meters (intra-habitat scale), hundreds of meters (intra-reef scale) and kilometre (supra-reef scale). We test the hypothesis that there are differences in richness, density and trophic structure within (habitat and micro-habitat) and between adjacent reef areas. A total of 60 species from 26 families were recorded at 375 senses video-transect (20 x 2m). The factorial analysis of variance showed significant differences in all spatial scales for data richness, density and density of trophic groups, noting a greater spatial variation in supra-reef (reefs) and intra-reef scale (habitat) compared to intra-habitat scale (micro-habitat), suggesting the existence of the influence of spatial scale in distribution and structure community. The results of canonical correspondence analysis (CCA) suggest an influence of habitat characteristics on the pattern distribution of the 25 most abundant species, although some species of fish exhibit behavior versatile. Among the variables identified, benthic cover and vertical relief were the most important factors for change in density of fish in the study area. Probably, these relationships occur in response to the complexity of the habitat, because environments complex offer greater availability of resources, shelters and a considerable amount of niches. Thus, this study suggests that a habitat characteristic, operating at different spatial scales, was the main factor responsible for structuring reef fish community on a local scale. However, further research is which are necessary to understand what processes and mechanisms may be governing this patterns.